Qualitative Research Methods: A Comprehensive Review of Tools and Approaches - M. V. Someswararao (AG Volumes, 2025)
Over the last few decades, qualitative research has changed dramatically in response to developments in technology, theoretical stances, and multidisciplinary methods. Exploring the breadth and complexity of social interactions, environmental factors, and human experiences is made possible by qualitative research. This review examines qualitative research methods, tools, and approaches with emphasis on their evolving nature in response to emerging digital technologies. The integration of artificial intelligence, virtual reality, cloud-based platforms, and audio-visual interview tools, accelerated by the COVID-19 pandemic, has enhanced the flexibility of qualitative inquiry. Core methods such as interviews, focus groups, observations, and document analysis remain central, supported by methodologies including grounded theory and ethnography. The increasing use of QDA software tools has transformed qualitative data analysis, highlighting the need for methodological awareness and technical competence among researchers.